Survival benefit of adding docetaxel, cisplatin, and 5-fluorouracil induction chemotherapy to concurrent chemoradiotherapy for locally advanced nasopharyngeal carcinoma with nodal Stage N2–3. (20th April 2017) - Kawahira, Masahiro; Yokota, Tomoya; Hamauchi, Satoshi; Onozawa, Yusuke; Ogawa, Hirofumi; Onoe, Tsuyoshi; Kamijo, Tomoyuki; Iida, Yoshiyuki; Nishimura, Tetsuo; Onitsuka, Tetsuro; Yasui, Hirofumi
Abstract : Induction TPF followed by CCRT might reduce distant metastasis, and may be feasible for the treatment of locally advanced nasopharyngeal carcinoma with nodal Stage N2–3. Abstract: Background: Concurrent chemoradiotherapy followed by adjuvant chemotherapy (CCRT-AC) has been established as the standard of care in locally advanced nasopharyngeal carcinoma (LA-NPC). The survival benefit of induction chemotherapy (ICT) for LA-NPC remains controversial. We analyzed the efficacy and feasibility of docetaxel, cisplatin and 5-fluorouracil (TPF) ICT followed by CCRT for LA-NPC with nodal Stage N2–3. Methods: We performed a retrospective analysis of 28 LA-NPC patients with nodal Stage N2–3 receiving induction TPF followed by CCRT (TPF group; n = 12) or CCRT-AC (CCRT group; n = 16) between October 2006 and May 2016. Results: The median follow-up periods were 36.4 (range 6.7–55.2) and 40.1 months (range 4.3–99.0) for the TPF and CCRT groups, respectively. One- and three-year overall survival for the TPF group vs. the CCRT group were 100% and 100% vs. 94% and 75%, respectively ( P = 0.21). The cumulative one- and three-year incidences of locoregional recurrence or progression for the TPF group vs. the CCRT group were 10% and 21% vs. 16% and 32% ( P = 0.49), and those of distant metastasis were 0% and 0% vs. 26% and 26%, respectively ( P = 0.08). The common Grade 3–4 acute toxicities were neutropenia, anorexia, febrile neutropenia, and stomatitis in the TPF group. The Grade 3–4 late toxicities did not differ significantly between the two groups. Conclusions: This study suggests that induction TPF followed by CCRT might reduce distant metastasis, so this combination may be feasible for the treatment of LA-NPC with nodal Stage N2–3.